ANALISIS PENGARUH ECCONOMIC VALUE ADDED (EVA), RETURN ON EQUITY (ROE), RETURN ON INVESTMEN (ROI) TERHADAP HARGA SAHAM PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BEI TAHUN 2020-2022.: ANALISIS PENGARUH EVA, ROE, ROI TERHADAP HARGA SAHAM PERUSAHAAN INDUSTRI BARANG KONSUMSI TAHUN 2020-2022. - Dwi Fitriyanto; Hafsari, Rania Naura; Hardina, Lulu; Ulynnuha, Ovi itsnaini (Jurnal Pijar, 2023)
The findings examine how economic value added, return on equity, and return on investment affect the stock prices of manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2020 to 2022. The linear regression method is required as a quantitative approach as well as secondary data. Based on the 2020–2022 era, there are 51 companies in the consumer goods industry sector. A total of 34 companies were collected through a purposive sampling approach, which involved a number of criteria and the determination of sample conditions. That way, the conclusion obtained is that economic value added has an effect on stock prices, while return on equity and return on investment have no effect on stock prices.